Respuesta :
Answer:
B. (x - 4)(x2 + 4x + 16)
Step-by-step explanation:
a3 – b3 = (a – b)(a2 + ab + b2)
substitute a=x n b=4 (cuz 64=4x4x4)
x3 - 64 = (x-4)(x2+4x+4x4)
= (x - 4)(x2 + 4x + 16)
The expression rewritten using difference of cubes as (x - 4)(x^2 + 4x + 16). Option b is correct.
Expansion of x^3 - 64 to be determine.
What is difference of cubes?
Difference of cube = [tex]a^3-b^3=(a-b)(a^2+ab+b^2)[/tex]
Here,
[tex]=x^3 - 64 \\=x^3-4^3[/tex]
a =x ; b = 4, put a and b in below equation,
[tex]a^3-b^3=(a-b)(a^2+ab+b^2)[/tex]
[tex]x^3-4^3=(x-4)(x^2+4x+16)[/tex]
Thus, the expression rewritten using difference of cubes as (x - 4)(x^2 + 4x + 16).
Learn more about difference in cubes here:
https://brainly.com/question/14473649
#SPJ5